Integrated Financial Governance Model with Budget Realization Information System - Andry Priharta; Nur Asni Gani; Jaharuddin Jaharuddin; Rony Edward Utama; Darto Darto; Medo Maulianza; Tri Ananto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
The research aims to identify the inhibiting factors for budget implementation and improve financial management through the development of an information system on budget realization at Universitas Berbasis Teknologi Modern (Modern Technology Based University - UBTM), a university in Banten focusing on modern technology. This is an applied research type with primary data obtained through focused group discussion using fishbone diagram analysis involving eleven informants. Based on the research, conditions and recommendations for improvement have been identified, which will then be prepared for the budget management flow process as the basis for preparing the budget realization information system. This system has set a monthly budget execution schedule, adequate internal control, and identified 34 work units with 91 users involved.